Luxembourg : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This paper studies the two vital issues of Luxembourg's economy: investment IMF-World Bank linkages and lessons and challenges in accommodating migrants and refugees. The Luxembourg investment fund industry, second in the world after the United States, has grown rapidly since the global financial crisis. Risks in investment funds are attracting global attention, and the linkages between Luxembourg funds and banks could contribute to transmitting financial volatility to the financial system and the real economy. Past experience of handling migration flows and a positive public attitude have helped the authorities to mobilize resources for accommodating sharply rising refugee inflows from mid-2015.